The life of George Eliot : a critical biography - Henry, Nancy, 1965- (Malden, MA : Wiley-Blackwell, 2012)
The life story of the Victorian novelist George Eliot is as dramatic and complex as her best plots. This new assessment of her life and work combines recent biographical research with penetrating literary criticism, resulting in revealing new interpretations of her literary work. A fresh look at George Eliot's captivating life storyIncludes original new analysis of her writingDeploys the latest biographical researchCombines literary criticism with biographical narrative to offer a rounded perspective.
The history of a writer : George Eliot and biographies -- Early years (1819-1849) -- London and George Lewes (1850-54) -- Marian Lewes and George Eliot (1855-59) -- Silas Marner and Romola (1860-64) -- Felix Holt, the radical and The Spanish gypsy (1865-69) -- Middlemarch (1870-72) -- Daniel Deronda (1873-76) -- Impressions of Theophrastus Such (1877-78) -- The final years : 1879 to Cross's life.
Includes bibliographical references and index.
Print version record.
Keywords: Eliot, George, -- 1819-1880.; Eliot, George, -- 1819-1880.; Eliot, George, -- 1819-1880; 1800-1899; Novelists, English -- 19th century -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Novelists, English; Electronic books; Biography; Electronic books